Psychometric Properties of the Arabic Version of the Problem Areas in Diabetes Scale in Primary Care - Sayed Ahmed, Hazem A.; Mohamed, Samar Farag; Elotla, Sally Fawzy; Mostafa, Mona; Shah, Jaffer; Fouad, Ahmed Mahmoud (Frontiers in Public Health, 2022)
Background The Problem Areas in Diabetes (PAID) scale is a reliable and valid tool that is widely used for diabetes-distress screening, but the Arabic version of the scale lacks validity and reliability analysis in primary healthcare (PHC) patients. This study aimed to evaluate the psychometric properties of the Arabic version of the PAID (AR-PAID) among Egyptian patients with type 2 diabetes mellitus (T2DM) in PHC settings. Methods We conducted a cross-sectional study on a convenience sample of 200 patients from 6 rural PHC settings in Ismailia governorate. The confirmatory factor analysis (CFA) was performed to test the goodness-of-fit to the predefined models of the PAID. Convergent construct was evaluated through correlations with the Arabic versions of Patient Health Questionnaire 9 (PHQ-9), Generalized Anxiety Disorder Scale (GAD-7), and 5-item World Health Organization Well-Being Index (WHO-5), in addition to glycated hemoglobin (HbA1c) level. Discriminant validity was evaluated through associations with patients' sociodemographic and clinical characteristics. Reliability was evaluated through internal consistency (Cronbach’s α) and test-retest reliability analysis (intraclass correlation coefficient, ICC). Results The CFA demonstrated the best fit to four-factor model. The AR-PAID was significantly correlated with the following measures: PHQ-9 (rho=0.71, p<0.001), GAD-7 (rho=0.50, p<0.001), WHO-5 (rho=-0.69, p<0.001), and HbA1c (rho=0.36, p<0.001), supporting sound convergent validity. Discriminant validity was satisfactory demonstrated. Internal consistency was excellent (α=0.96) and test-retest reliability was stable (ICC=0.97). Conclusions The AR-PAID scale is a valid and reliable instrument for diabetes-distress screening in primary care patients with T2DM that can be used in clinical settings and research. Further research is needed to validate a short form of the AR-PAID scale.